Innovations in inductively coupled plasma-mass spectrometry: bridging scientific fields - Hassen, Jasim; Silver, Jack (Journal of Medical Science, 2025)
Inductively coupled plasma mass spectrometry ICP-MS is a versatile analytical tool with several research uses and regular applications in many domains, including biological materials, environmental analysis, and geochemistry. This technique detects trace components in water, soil and clay, blood, urine, pharmaceutical products, and medicinal cases. Although other methods, such as atomic absorption and atomic emission, are still used by researchers, there has been a noticeable shift toward ICP-MS, notably over the last decade. Developing accurate and precise methods for measuring components at low concentrations is crucial for detecting abnormalities in the human body and detecting trace amounts of metal in many other species. ICP-MS is a viable approach for the elemental determination of biological fluids, water, clay, and pharmaceuticals because it allows for reliable analysis at trace and ultra-trace levels while maintaining a wide dynamic range. Many breakthroughs have been made in ICP-MS analytical capabilities over the last few years. This review discusses the most recent works that use trace element analysis by ICP-MS in several fields.
Keywords: ICP-MS; water; clay; blood; urine